Prevention of silica health effects in Italy: current challenges for the occupational health and safety Unit of the Italian National Health Service / Prevenzione degli effetti sulla salute della silice in Italia: le sfide attuali per i servizi di medicina e sicurezza sul lavoro del Servizio Sanitario Nazionale - Giovanazzi, A.; Chellini, E.; Fubini et al., B. (La Medicina del Lavoro, 2011)
Summary Background: Since its foundation in 2002, the Italian Silica Network (NIS), a collaborative network of professionals and public authorities, has been engaged in several aspects of research, control, and prevention of silica exposure and effects, and also in support for compensation claims for silica-related occupational health effects in Italy. Methods: We start with a report on the NIS point of view concerning the recent scientific results (from epidemiology and laboratory studies), including those carried out by NIS in cooperation with Italian universities and other public agencies. This is followed by a description of the data on silica exposure in different Italian workplaces and guidelines for the management of occupational exposure to silica, as developed by two model regional programmes for the ceramics industry, metal foundries and tunnel excavation. Results: The NIS initiatives highlighted the persistence of workplace conditions posing a significant risk for silica-related health effects, particularly in small industries and workshops. Experimental work has also shown that a number of physical and chemical factors affect the bioreactivity of silica particles. Conclusion: Based on NIS experience, it appears clear that currently conditions exist in Italy so as to positively contribute to the WHO Programme for the eradication of silicosis and the other diseases related to silica exposure. In order to achieve this goal, a coordinated and wide-ranging effort is required to reduce the wide gap in specific prevention activities, particularly in small industries and workshops, where high levels of silica exposure sometimes occur.